Image enhancement process on digital radiographic image with weld discontinuities / Shahidan Mohamad and Suhaila Abd Halim - Mohamad, Shahidan; Abd Halim, Suhaila (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Non Destructive test (NDT) is the most popular and commonly used method to evaluate the condition of the test target area without damaging it properties. In welding industry, the purpose of NDT is to inspect and evaluate the existing of discontinuity in the joining part that cannot be seen by naked eyes. Due to the problem poor quality of radiographc image during data acquisition, this research aims to develop image enhancement process in order to improve and analyze the quality of the radiographic image. A low quality of image is enhanced using image processing methods for better image visualization. The methods used are noise removal and contrast adjustment using circular average filter and logarithmic intensity contrast respectively. For continuity detection, edge detection and thresholding with morphological structuring element are applied. The performance and accuracy of the segmented image is determined using Receiver Operating Characteristics (ROC). Results indicate that the quality of the image is improved and the welding discontinuity is successfully extracted. The implementation reduces the time consuming and cost spending in NDT process besides helps the radiographer in inspecting and evaluating a discontinuity accurately.